Misrecognized Violence against Women and Perpetrated by Women. Seeking Remedies - Joanna Dutka (Ethics in Progress, 2014)
This paper explores the misrecognition of women's experience with violence in order to understand better what kinds of approaches to the problem would make it possible to design successful strategies for the prevention of violence. Violence itself, as well as common misconceptions regarding its mechanisms, carries ramifications that go far beyond direct and physical injury. The prevalence of violence and lack of social awareness regarding its mechanisms result in limitations to the social participation of many individuals and groups. Among the groups affected, women have an important place, both due to their number and the way that femininity relates to and disturbs other identities.